Molecular and Culture-Based Analyses of Aerobic Carbon Monoxide Oxidizer Diversity† - King, Gary M. (American Society for Microbiology, 2003)
Isolates belonging to six genera not previously known to oxidize CO were obtained from enrichments with aquatic and terrestrial plants. DNA from these and other isolates was used in PCR assays of the gene for the large subunit of carbon monoxide dehydrogenase (coxL). CoxL and putative coxL fragments were amplified from known CO oxidizers (e.g., Oligotropha carboxidovorans and Bradyrhizobium japonicum), from novel CO-oxidizing isolates (e.g., Aminobacter sp. strain COX, Burkholderia sp. strain LUP, Mesorhizobium sp. strain NMB1, Stappia strains M4 and M8, Stenotrophomonas sp. strain LUP, and Xanthobacter sp. strain COX), and from several well-known isolates for which the capacity to oxidize CO is reported here for the first time (e.g., Burkholderia fungorum LB400, Mesorhizobium loti, Stappia stellulata, and Stappia aggregata). PCR products from several taxa, e.g., O. carboxidovorans, B. japonicum, and B. fungorum, yielded sequences with a high degree (>99.6%) of identity to those in GenBank or genome databases. Aligned sequences formed two phylogenetically distinct groups. Group OMP contained sequences from previously known CO oxidizers, including O. carboxidovorans and Pseudomonas thermocarboxydovorans, plus a number of closely related sequences. Group BMS was dominated by putative coxL sequences from genera in the Rhizobiaceae and other α-Proteobacteria. PCR analyses revealed that many CO oxidizers contained two coxL sequences, one from each group. CO oxidation by M. loti, for which whole-genome sequencing has revealed a single BMS-group putative coxL gene, strongly supports the notion that BMS sequences represent functional CO dehydrogenase proteins that are related to but distinct from previously characterized aerobic CO dehydrogenases.